An evaluation of the compression strength of gypsum according to proportion and manipulation - Paulo E. C. Cardoso; Paulo A. Burmann; Luciano Anziliero; Jomara M. F. S. Cardoso; Andréa U. Tavares; Fernanda T. Sadek (Brazilian Dental Science)
This study evaluated the compression strength of gypsum type IV and V according to 2 variables: 1) water proportioned randomly or as recommended by the manufacturer and 2) according to 3 (three) different groups of operators (dentists, technicians and dental students). 180 specimens, produced according to ADA regulation nr. 25 underwent, after seven days (dry resistance), the compression strength test in an universal testing machine. After statistical analyses of the data, there was no statistical significant difference regarding the group of operators. Regarding the variable proportion, the specimens manufactured using a random proportion of water/gypsum powder presented a lower compression value (626,2 Kgf/cm2) when compared to the group where the amount of water/gypsum powder followed the recommendation of the manufacturer (741,7 Kgf/cm2). This difference was statistically significant (p<0.01).